Prevalence and associated factors of needlestick and sharp object injuries among healthcare workers in Ethiopia: a systematic review and meta-analysis - Kaweti, Gudeta; Feleke, Tihun (Frontiers in Epidemiology, 2024)
ABSTRACT Background: Needle-stick and sharps injuries affect Healthcare workers. However, there are limitations of evidence for informed decision-making by stakeholders since individual research shows inconsistent results. Therefore, this study set out to assess the pooled prevalence of Needle-stick and sharps injuries and associated factors. Methods: MEDLINE/PubMed, EMBASE, Web of Science, Google Scholar, and others were searched from 5, September 2023 to 10, October 2023. "Prevalence" OR "Burden" OR "Magnitude" AND "Associated factors" OR "related factors" OR "Risk factors" OR "determinants" OR "Predictors" AND "Needle stick Injury" OR "Sharp Injury" OR "Health care Workers" OR " Health Care Personnel" OR "Nurses" OR "Professional" AND "Ethiopia" Results: The pooled prevalence of needle sticks and sharp objects injury was 40.01 (95% CI: 34.72, 45.30). Needle-stick recapping (AOR= 2.51; 95% CI: 1.72, 3.66, P<0.001), absence of routine precaution (AOR= 2.20; 95% CI: 1.25, 3.86, P<0.01) and lack of training (AOR=2.41; 95% CI: 1.47, 3.95, p<0.001) had increased odds of needle-sticks and sharp objects injury Conclusion: 40% of healthcare workers in Ethiopia faced needle sticks and sharp objects injury. Recapping, absence of routine precautions, and lack of training were the factors. Keywords: needle sticks injury, sharp Objects injury, Pooled prevalence, Systematic review, Meta-analysis, Ethiopia